Investigating the sensing mechanism of flexible silicon nanowire gas sensors for acetone detection - Huancong Peng; Kuibo Lan; Guoxuan Qin (AIP Advances)
With the rapid development of nanotechnology, silicon nanowire (SiNW) array gas sensors have shown great potential for gas detection due to their high sensitivity, fast response, and excellent selectivity. In this study, we fabricated a flexible SiNW array gas sensor and measured its performance in acetone gas detection under various conditions, including different acetone gas concentrations (ranging from 0.1 to 200 ppm), humidity levels, and bending conditions. To further investigate the sensor’s performance, we developed a multiphysics finite element model using COMSOL software. The model simulation results were in good agreement with the experimental data. Experimental and modeling results showed that the main factors influencing sensor performance were the changes in nanowire morphology, diffusion dynamics, and adsorption, while the underlying mechanisms were discussed. This study provides helpful theoretical support for the design and optimization of flexible SiNW array gas sensors, offering insights for the development of highly sensitive and durable flexible gas sensors.